Resistance of Pseudomonas Aeruginosa From Clinical and Environmental Sources to Heavy Metals in Hilla City, Iraq - Al-Charrakh, Alaa H.; Al-Enzi, Raafet M. (Science Journal of University of Zakho, 2014)
The study included 300 samples collected from 150 clinical and 150 hospital environmental sources. Only 43 (14.3%) isolates belonged to Ps. aeruginosa. The isolates were tested for their susceptibility to 7 types of heavy metals (HM) namely Copper Sulfate, Silver Sulfate, Mercury chloride, Lead nitrate, Zinc sulfate, Cadmium sulfate, and Nickel sulfate. The screening test for ability of the isolates to resist HM was detected using lead nitrate in concentration of 400μg/ml. Results revealed that 37/43 were resistant to lead nitrate (400μg/ml). The MIC of 7 HM was detected by agar dilution and pouring method. Results revealed that most of the isolates were resistant to 7 HM in some of concentrations. The plasmid content was investigated for all 37 isolates of Ps. aeruginosa (34 clinical and 3 environmental). Results revealed that most isolates 32/37 harbored large (mega) plasmid. Biofilm production of Ps. aeruginosa isolates was investigated; results showed that 20/43 (47%) of isolates had biofilm. This study concluded that the increase of HM resistance was correlated with biofilm production for some HM used. The bacterial curing is proceeding for one isolate of Ps. aeruginosa (Ps.3). The results showed survived resistance to all HM used, which may be due to HM resistance trait was carried out on bacterial chromosome rather than plasmid.